English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-01-25 12:42:44 · 5 answers · asked by jmayer8921 1 in Science & Mathematics Mathematics

5 answers

this is the answer if the question was 4^(3X)=6^(2X+5) (this is easy):

first you should take the 'ln' of both sides:

ln4^(3X)= ln6^(2X+5)

ln4^(3X) is equal to (3X)ln 4

and 6^(2X+5) is equal to (2X+5)ln 6

so: (3X)ln4=(2X+5)ln6

now expand the (2X+5)ln6:

it will be (2X)ln6+(5)ln6

so: (3X)ln4=(2X)ln6+5ln6

then its just a matter of basic algebra:

now get the expressions that contain X's on one side, and the rest on the other (with being careful of the signs):

(3X)ln4 - (2X)ln6 = 5ln6

now taking X as the common factor of the left side:

(X)(3ln4 - 2ln6) = 5ln6

so: X= 5ln6 / (3ln4 - 2ln6)

calculating this gives:

X=15.5706563 or 15.57 for short.

and there you have it.

i hope that helped.

2007-01-25 13:31:58 · answer #1 · answered by cool snoopy 1 · 0 0

put all like terms on one side. all numbers to your right and the 2x to the left of the = sign. 3x-2x=6+5-4 you can do the rest.

2007-01-25 20:49:11 · answer #2 · answered by Mr. Sir 5 · 0 0

Well assuming you have the formula written correctly first raise your 4^3 x= 64x do the same toh 6^2x = 36x you should now have:

64x = 36x + 5

subtract 36x form both sides to get 28x = 5

now divde by 28 on both sides x = about .18

2007-01-25 21:18:31 · answer #3 · answered by ikeman32 6 · 0 0

I would help but I'm not quit that smart yet....but I have a tip...Start with what you know...and go from there!

2007-01-25 20:49:18 · answer #4 · answered by Ducky 2 · 0 0

no lazybones

2007-01-25 20:48:44 · answer #5 · answered by Sean C 2 · 0 0

fedest.com, questions and answers